2011
DOI: 10.1007/978-1-61779-520-6_14
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging SBDD in Protein Therapeutic Development: Antibody Engineering

Abstract: Antibodies make up the largest, growing segment of protein therapeutics in the pharmaceutical and biotechnology industries. The development or engineering of therapeutic antibodies is based to a large extent on our knowledge of antibody structure and requires sophisticated methods that continue to evolve. In this chapter, after a review of what is known about the structure and functional properties of antibodies, the current, state-of-the-art antibody engineering methods are described. These methods include an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 141 publications
0
33
0
Order By: Relevance
“…In the crystal structure of PA1 and mAb 2H1, the parts of the peptide located in the binding pocket of 2H1 correspond to two motifs involving Thr-5 and Pro-6 and Trp-8, Met-9, and Leu-10, which are comparable with two motifs in P1 that show the greatest decreases in binding when mutated to alanine. Because these studies were done with immobilized peptide, some differences in binding observed for IgG 1 and IgG 3 may reflect a loss of avidity resulting from an inability to form binding complexes given Ab isotype-related differences in hinge angles (41). However, we think this explanation is less likely to apply for all isotypes given the strong reactivity of the IgG 2a and IgG 2b subclasses, with both GXM and P1 (7).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In the crystal structure of PA1 and mAb 2H1, the parts of the peptide located in the binding pocket of 2H1 correspond to two motifs involving Thr-5 and Pro-6 and Trp-8, Met-9, and Leu-10, which are comparable with two motifs in P1 that show the greatest decreases in binding when mutated to alanine. Because these studies were done with immobilized peptide, some differences in binding observed for IgG 1 and IgG 3 may reflect a loss of avidity resulting from an inability to form binding complexes given Ab isotype-related differences in hinge angles (41). However, we think this explanation is less likely to apply for all isotypes given the strong reactivity of the IgG 2a and IgG 2b subclasses, with both GXM and P1 (7).…”
Section: Discussionmentioning
confidence: 97%
“…The V region binds antigen (Ag) and is capable of enormous combinatorial diversity that can recognize a myriad of molecular conformations, whereas the C region provides such functional capacities as the ability to interact with host receptors and activate the complement system (1). In this conception, the V and C regions functioned as two virtually independent domains, with the V region being responsible for binding Ag and the C region providing other biological functions.…”
mentioning
confidence: 99%
“…These antibodies may present liabilities with regard to the development of therapeutic antibodies. 30 Twelve-residue loops of IM sample are also rich (~65%) in Cys at position 95 and 95e, probably making of disulfide bridge. The content of Cys at those positions drops to ~20% in the BM and SP samples, suggesting a positive pressure by the peptide immunization to select for loops with a disulfide bridge between position 95 and 95e.…”
Section: Vκ Repertoirementioning
confidence: 99%
“…6,7 Many of these platforms depend on antibodies obtained by animal immunization, e.g., via the hybridoma technique, 8 and often require subsequent optimization. 9,10 Humanization, required for most antibodies from animal sources, typically leads to a reduction in affinity. Other modifications may also be also introduced in order to modulate other properties such as thermal stability, water solubility, pharmacokinetics, etc., which often results in partial losses of the original antigen-binding affinity.…”
Section: ■ Introductionmentioning
confidence: 99%